Immune Modulation of Metastatic Niche Formation in the Bone - Cheng, Xinyu; Wang, Zhan (Frontiers in Immunology, 2021)
Bone metastasis is commonly seen in patients with breast cancer, prostate cancer and lung cancer. Tumor-intrinsic factors and the tumor microenvironment cooperate to affect the formation of bone metastatic niche. Within the bone microenvironment, immune cells have been regarded as a major contributor to metastatic progression. In this review, we describe the dynamic roles of immune cells in regulating metastatic homing, seeding, dormancy, and outgrowth in the bone. We also summarize the diverse functions of immune molecules including chemokines, cytokines, and exosomes in remodeling the bone metastatic niche. Furthermore, we discuss the therapeutic and prognostic potential of these cellular and molecular players in bone metastasis.